Identifikasi Kualitas Udara di Sekitar PLTU Teluk Sepang, Kota Bengkulu - Verojenases, Fascal; Angeli Silaban; Samuel Christian Alfredo Banjarnahor; Irkhos; Lizalidiawati (Jurnal Fisika Unand, 2025)
PLTU Teluk Sepang uses coal as the main fuel and has the potential to reduce air quality in the vicinity. This study aims to identify the air quality around PLTU Teluk Sepang and its impact on the environment and public health. The data used are PM2,5, PM10, CO, and CO2 at seven location points in June and July 2024. The method in this research is quantitative and descriptive, quantitative is used to compare the measurement results with the threshold set by the government, while descriptive is used to visualize the data in the form of graphs and distribution maps. The results showed that PM2,5 and PM10 levels at several points exceeded the specified thresholds, especially near the PLTU and traffic road areas, which fell into the “Unhealthy.” category. CO levels are still within safe limits, while CO2levels are in the polluted air category, and the increase in pollutants at night indicates a significant impact of PLTU activities on air quality. This study shows that the air quality around Teluk Sepang PLTU is in a polluted condition, so mitigation measures are needed to control air pollution for public health and the environment.